2017
DOI: 10.1093/jee/tox029
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptional Analysis of the Host-Specialized Aphids Aphis gossypii (Hemiptera: Aphididae)

Abstract: Host specialization is an ubiquitous character in aphid populations. Many polyphagous aphid populations usually consist of several subpopulations that have strong fidelity to a specific host or a subset of host range. Host specialization is an evolutional result of food habit of insects. However, genetic basis and molecular mechanism of host specialization are still unclear. In this study, we presented a comparative analysis on global gene expression profiles of three lineages of Aphis gossypii Glover: cotton-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…However, more than 15,000 genes (>40%) were found to be differentially expressed when these two populations were compared to the population feeding on the novel host cowpea. This time, the differentially expressed genes were mostly enriched in the KEGG super-pathways "organismal systems" and "cellular processes," indicating a significant stress-response (Zhang et al, 2017). It is interesting to note that this response was quite similar in its characteristics to the non-adaptive plastic response that "Type IV" B. tabaci species presented when switching to feed on a novel/non-suitable host plants ( Figure S3d), raising the possibility for the existence of an hemipteran common "stress-response tool-box.…”
Section: Discussionmentioning
confidence: 99%
“…However, more than 15,000 genes (>40%) were found to be differentially expressed when these two populations were compared to the population feeding on the novel host cowpea. This time, the differentially expressed genes were mostly enriched in the KEGG super-pathways "organismal systems" and "cellular processes," indicating a significant stress-response (Zhang et al, 2017). It is interesting to note that this response was quite similar in its characteristics to the non-adaptive plastic response that "Type IV" B. tabaci species presented when switching to feed on a novel/non-suitable host plants ( Figure S3d), raising the possibility for the existence of an hemipteran common "stress-response tool-box.…”
Section: Discussionmentioning
confidence: 99%
“…RNA extraction and cDNA synthesis for each sample were conducted following the above-mentioned method. The gene NADH was chosen as the reference gene because of its consistent expression in all samples in this study and in our previous studies [ 96 ]. Specific primers for each gene were designed by using Beacon Designer version 8.0 (Premier Biosoft, Palo Alto, CA) (Table S 6 ).…”
Section: Methodsmentioning
confidence: 99%
“…Specific primers for each gene were designed by using Beacon Designer version 8.0 (Premier Biosoft, Palo Alto, CA) (Table S 6 ). As described in [ 96 ], 20 ÎŒL volume reactions contained 10 ÎŒL SYBR Premix Ex Taq II (TaKaRa), 2 ÎŒL cDNA, 1 ÎŒL each forward and reverse primer (10 ÎŒM), and 6 ÎŒL ddH2O. All qRT-PCR reactions were performed on a Roche LightCyclerÂź 480 II system (Roche Diagnostics Ltd., Rotkreuz, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…High rates of positively selected genes in CPB, L. tumamoca and L. peninsularis , are notable as these species expanded onto host plants, with L. tumamoca and L. peninsularis expanding into families outside of Solanaceae (Jolivet et al 1988). Recent experiments have shown dramatic regulatory changes in detoxification pathways following host shifts in plant‐feeding arthropods (Dermauw et al., 2013; Govind et al., 2010; MĂŒller et al., 2017; Yu et al., 2016; Zhang et al., 2017). Additionally, other comparative genomic studies have found similar evidence of positive selection in detoxification genes related to host plant utilization (Simon et al., 2015; Gloss et al, 2019; Okamura et al., 2019).…”
Section: Discussionmentioning
confidence: 99%